2015
DOI: 10.3390/sports3020103
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Running Performance of Athletes with Lower-Limb Amputation at the Paralympic Games 2004–2012

Abstract: This paper analyses the performances of lower-limb amputees in the 100, 200 and 400 m running events from the 2004, 2008 and 2012 Paralympic Games. In this paper, four hypotheses are pursued. In the first, it investigates whether the running performance of lower-limb amputees over three consecutive Paralympic Games has changed. In the second, it asks whether a bi-lateral amputee has a competitive advantage over a uni-lateral amputee. In the third, the effect of blade classification has been considered and we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Reducing the number of medals may not mean a decrease in performance. The study by Hassani et al [ 79 ] did not find differences in the performance of amputees from 2004 to 2012. Since Paralympic sport has increased interest, increased participation (more athletes and new participating countries) and a greater commitment by countries make the distribution of medals among the countries greater [ 80 ].…”
Section: Discussionmentioning
confidence: 93%
“…Reducing the number of medals may not mean a decrease in performance. The study by Hassani et al [ 79 ] did not find differences in the performance of amputees from 2004 to 2012. Since Paralympic sport has increased interest, increased participation (more athletes and new participating countries) and a greater commitment by countries make the distribution of medals among the countries greater [ 80 ].…”
Section: Discussionmentioning
confidence: 93%
“…Further concerns have been raised about how this technology will be judged in the future to ensure ethical inclusion of such technology in disability sports [14]. This is also substantiated by Hassani et al [15], who showed statistically that bilateral amputee using ESR feet dominated the Paralympic Games post 2008, when these ESR feet were first introduced.…”
Section: Introductionmentioning
confidence: 95%
“…Validity of the performance analysis of an event has been extensively supported (Hughes and Bartlett 2002) and has been applied to sport with limb absence with measurable impacts on how its technology should be viewed (Hassani et al 2015;Dyer 2017).…”
Section: Model Validity and Reproducibilitymentioning
confidence: 99%